Pyridoxine-Induced Sensory Neuropathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
An 18-year-old man with seizures from birth was followed in the Department of Clinical Neurological Sciences, University of Western Ontario, London, and was found to have developed a sensory neuropathy by 2 years of age following treatment with pyridoxine in doses up to 2000 mg/day.